The role of digitalization in driving green growth: A global panel data perspective - Muhammad Tariq Majeed; Fatima Sharif (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This paper analyzes the green growth (GG) effects of digitalization using panel data from, 164 countries spanning the period from 1990 to 2023. The study uses four measures of, digitalization: internet users, broadband, mobile cellular, and fixed telephone, subscriptions. The empirical results are estimated employing pooled ordinary least squares,, fixed effects, random effects, system generalized method of moments, and panel quantile, regression estimation approaches. STATA software is used to analyze the data. The results, suggest that the proliferation of digitalization measures tends to boost GG. The results, based on principal component analysis also confirm the positive impact of digitalization, on GG. Furthermore, the GG-improving influence of digitalization remains robust across, all quantiles. The role of renewable energy also turns out to be conducive to improving GG, prospects. However, the roles of financial development and trades are not robust in, influencing GG. The GG effects of financial development vary from a positive influence, at lower quantiles to a negative influence at higher quantiles. Conversely, the GG effect of, trade varies from a negative influence at lower quantiles to a positive influence at higher, quantiles.
Keywords: 330; Digitalization; carbon emissions; financial development; renewable energy consumption; trade openness